A systematic review on the outcome of distraction osteogenesis in TMJ ankylosis - Ankita Chugh; Divya Mehrotra; Pradeep K. Yadav (Elsevier, 2021)
Introduction: TMJ ankylosis (TMJa) management by arthroplasty alone fails to address the deformity and the compromised airway. Distraction osteogenesis (DO) can offer a pragmatic solution to TMJa. The aim of the study was to generate evidence towards the role of DO in TMJa, evaluate its efficiency and develop an algorithm for use of DO in TMJa. Material and methods: The research question was formulated using the PICOS statement for reporting guidelines in systematic reviews, where the efficiency of DO was evaluated in terms of mouth opening, correction of facial deformity and asymmetry, airway correction, and its long term effects. Results: 1130 articles reported DO as a treatment modality for TMJ ankylosis, of which 32 prospective studies, 16 retrospective and 2 RCTs were included in the study. DO was used for mandibular distraction in 45 studies and for simultaneous maxillamandibular distraction in only five studies. An algorithm for use of DO in TMJa was developed. Conclusion: Although DO has proven its application in TMJ ankylosis cases, its best use is for correction of obstructive sleep apnoea. Relapse causing loss of posterior ramal height is a concern after transport DO. Prearthroplastic DO appears to best correct mandibular deformity. A maxillomandibular deformity requires simultaneous maxillomandibular distraction. However, a metanalysis is still awaited for effectiveness of DO in TMJ ankylosis.